Two-dimensional binary mixtures of patchy particles and spherical colloids. Issue 47 (11th November 2016) - Słyk, Edyta; Rżysko, Wojciech; Bryk, Paweł
Abstract : Quasicrystals are some of the ordered phases found in two-dimensional mixtures of spherical and patchy colloids. Abstract : Using Monte Carlo simulation we study two dimensional mixtures of patchy and spherically symmetric particles. Such mixtures can be synthesized experimentally by covering colloids with appropriate types of DNA strands [L. Feng, et al., Adv. Mater., 2013, 25, 2779]. We focus on finding out the ordered structures that can be formed in such systems. The type of ordered phase strongly depends on the valency, size and binding energy of the patchy particles. If the patch size is small enough, i.e. it allows only one spherically symmetric particle to be bound, the ordered structure follows either a hexagonal or a tetragonal pattern depending on the valency of the patchy particles. Moreover, we find stable quasicrystals of dodecagonal symmetry. Additional structures can be obtained if the patches are larger and the binding energy is higher. Depending on the valency of the patchy particles we find either lanes or branched structures forming polygons of the spherically symmetric particles with few patchy particles inside. For pentavalent patchy particles we find stable quasicrystals of decagonal symmetry.